Investigating Students’ Speaking Fears in Making English Video Project - Prayudha.S, Joko (Journal of Language, Literature and Teaching, 2023)
Speaking skills are one of the most productive language skills. Where the speakers will produce an utterance through the means of speech. In the implementation of learning, sometimes there are still many students who feel afraid to speak English, even though speaking ability is very important to create good two-way communication. This study aims to investigate the speaking fears that students experience when making English video projects. The method used in this research is descriptive-qualitative. The participants in this study were 35 high school students who learned English through an English video project. The data were obtained through direct observation and interviews with several students regarding the fears they experienced when making an English video project. Data analysis through data reduction, data display, and conclusion. The results of the study show that there are still many students who feel afraid when speaking English and making English videos. The factors that influence this fear include background knowledge, messy grammar, embarrassment, and a lack of confidence, as well as feelings of pressure when practicing conversations in English through making English videos.